DEM ALÍW HUQÍQÍ HÁM ONÍ TÁRTIPKE SALÍWDÍŃ HUQÍQÍY TIYKARLARÍ - Tilewov, E. (SCIENCE and SOCIETY, 2024)
Article Constitution of the Republic of Uzbekistan, Labor Code of the Republic of Uzbekistan, decrees and resolutions of the President, bases of officials of the Republic of Uzbekistan, labor holidays, labor holidays. Labor workers may be released for some time, and volunteers may be released for some time.